Structural Equation Modeling Approach to Elucidate the Impact of IMC on Brand Equity in Life Insurance Industry - Gupta, Omdeep; Nasser, Kaynat; Biswas, Nibedita (Indian Journal of Marketing, 2012)
This paper investigates the impact of Integrated Marketing Communication in building Brand Equity in Life Insurance Industry by using components of IMC and Brand Equity. Further, this research is valuable in finding how the consumer perceives and is aware of the brand by different marketing communication programmes. IMC can make the communication with an organization’s target audience more efficiently and effectively, thus enabling the formation of brand awareness and brand image, and ultimately leading to higher brand equity and enhancing the customer accessibility & forms an organizational value. SEM is used for testing the hypothesis, as it is the best multi-variant procedure for testing both the construct validity and the theoretical relationship.